Measuring the relative efficiency of quality management practices in Turkish public and private universities - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
Using data envelopment analysis (DEA) in conjunction with stochastic frontier analysis (SFA), the aim of this study was to measure the relative efficiency of quality management (QM) practices in Turkish public and private universities. Based on the extant literature, a set of nine critical QM factors and seven performance indicators for Turkish universities were identified as input and output variables, respectively. SFA confirmed the existence of significant relationships between QM factors and performance indicators. DEA findings indicated that private universities with higher levels of QM efficiency on stakeholder-focus indicators achieved better performance in terms of fulfilling the expectations of their stakeholders. In contrast, public universities were more successful in managing QM practices for a superior teaching and research performance. Finally, after eliminating the managerial discrepancies, no significant structural efficiency difference was found between these two groups of universities through stakeholder-focus model, though some significant variation was noted in both factor-efficiency and total-efficiency models. As for total-efficiency model, we may infer that the structural differences found in favour of public universities for factor-efficiencies are counterbalanced by private universities which tend to focus more on their stakeholders in managing QM applications.
Keywords: data envelopment analysis; stochastic frontier analysis; quality management; public and private universities; Turkey; DATA ENVELOPMENT ANALYSIS; HIGHER-EDUCATION INSTITUTIONS; STOCHASTIC FRONTIER; UK UNIVERSITIES; PERFORMANCE; DEA; TQM; BENCHMARKING; MODEL; US